NUCLEAR DEBATES IN ASIA : the role of geopolitics and domestic processes - Mochizuki, Mike; Ollapally, Deepa Mary (Rowman & Littlefield, 2016)
"The rise in global demand for nuclear energy is heavily concentrated in emerging and aspiring Asian powers who also happen to be at risk for high stakes nuclear weapons competition, nuclear conflict, and nuclear terrorism. This is compounded by rising geopolitical tensions in Asia, with more assertive policies in the region testing regional stability. How can we understand nuclear energy and nuclear weapons trajectories in Asia and how they are being shaped? This book asserts that we need to go beyond conventional international systems explanations and look at the domestic sphere to gauge Asia's nuclear outlooks. The authors analyze domestic debates and discourse on nuclear energy, nuclear security and nuclear non-proliferation in China, India, Japan, Pakistan, South Korea, Taiwan, Vietnam and the Association of Southeast Asian Nations (ASEAN). They explore what drives the debates and how decisions are framed; what the interplay is between domestic dynamics and geopolitical calculations in the discourse; where the center of gravity of debates lies; and what this means for regional cooperation or competition, and U.S. nuclear policy in Asia. This book finds that despite the increasing geopolitical competition in Asia, the center of gravity of debates on nuclear weapons and energy is trending toward pragmatic Realist-Globalist perspectives, from more unstable Nationalist-Realist outlooks. Nuclear weapons discourse shows surprising continuity favoring non-provocative postures under strong civilian control. We find lower than expected salience for energy security arguments and higher than expected challenges in the popular arena to nuclear energy"